Energy and noise characteristics of a SEPIC buck-boost converter with unipolar and bipolar output - V. P. Babenko; V. K. Bityukov (Российский технологический журнал)
Some advantages of the SEPIC buck-boost converter makes it stand out from other configurations. It makes possible to obtain from a unipolar input voltage both unipolar and bipolar output voltage with a good symmetry between positive and negative output voltages. It also provides efficient performance as well as circuit simplicity in unipolar and bipolar topology owing to the use of a single switch which can be operated by available integrated controllers of boost converters. The article considers the topologies of a SEPIC buck-boost converter built according to the traditional scheme (with two inductors) and according to the scheme on magnetically coupled chokes. To analyze the processes and factors affecting the converter operation efficiency, a circuit simulation has been done using the Electronics Workbench. The results of the investigation of a pulsed DC converter of input voltage to unipolar or bipolar output voltage using SEPIC buck-boost topology are presented. The circuit simulation enables to specify the switching process characteristics, to estimate the ripple level of the input current and its spectral characteristics, and to develop recommendations concerning the choice of parameters of converters elements and generation of control signals. Based on the simulation results, the load, control, and noise characteristics of the converter are obtained. The level of symmetry of positive and negative output voltage is investigated for the converter on discrete and magnetically coupled chokes. The assessment of the effect of leakage inductance on converters with magnetic coupling of inductive elements is given. Examples of practical implementation of converters built according to the SEPIC topology are shown. It is found that the resistance of the choke windings, which is less than 0.5 Ohm, has practically no effect on the efficiency of the converter, retaining the factor of about 0.9 in a wide range of load currents, while the main source of conversion losses is a passive diode switch. Synchronous converter circuits of a number of manufacturers are more efficient, but require more complex controllers for active switches with elements for protection against through currents.